1996
DOI: 10.1007/bf01718612
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expression of HA-NA combinations in human-avian influenza A virus reassortants

Abstract: Human-avian and human-mammalian influenza A virus reassortant clones with the neuraminidase (NA) gene of the A/USSR/90/77 (H1N1) strain and hemagglutinin (HA) genes of H3, H4 and H13 subtypes had been shown in an earlier publication to produce low HA yields in the embryonated chicken eggs. The low HA titers had been shown to be due, at least in part, to the formation of virion clusters at 4 degrees C; the clustering was removed by the treatment with bacterial neuraminidase [Rudneva et al., Arch. Virol (1993) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Otherwise, the enhanced receptor binding is a serious disadvantage in the late stage of infection because it prevents the release of progeny viruses from host cells. The need for such a match of HA and NA activities had so far only been deduced from studies analyzing natural virus isolates or laboratory-generated reassortants (15,16,22,32). Taken together, our data represent the first concise study of the functional interrelationship of distinct HA and NA species and provide experimental evidence for the strict requirement of a fine tuning of HA receptor-binding and NA receptor-destroying activity in order to allow efficient influenza virus propagation (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Otherwise, the enhanced receptor binding is a serious disadvantage in the late stage of infection because it prevents the release of progeny viruses from host cells. The need for such a match of HA and NA activities had so far only been deduced from studies analyzing natural virus isolates or laboratory-generated reassortants (15,16,22,32). Taken together, our data represent the first concise study of the functional interrelationship of distinct HA and NA species and provide experimental evidence for the strict requirement of a fine tuning of HA receptor-binding and NA receptor-destroying activity in order to allow efficient influenza virus propagation (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…When different natural and laboratory-derived influenza viruses were analyzed for their HA and NA composition, it was striking to see that some combinations of antigenic subtypes occurred quite frequently while others were never detected (18,32). In the latter case, the failure to produce stable highyield reassortant strains with some HA and NA combinations has been attributed to an incompatibility between the opposing activities of these two glycoproteins leading to viral aggregation.…”
mentioning
confidence: 99%
“…One possible reason may be that HA-NA incompatibility is responsible for inefficient replication of the rIndo/rEgret NA reassortant virus in 293T cells or ECEs. The HA and NA proteins of influenza work together to efficiently bind and release virus from the cells during replication, and it is known that HA-NA incompatibility can result in inefficient viral replication or aggregation on the cell (10,44). The importance of a balanced HA-NA relationship often results in the coevolution of NA along with changes in HA of influenza viruses to maintain a functional unit (34,35,57).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that sequences in the 3Ј and 5Ј ends of the coding regions within the HA (the present study), NA (6), M (J. Maeda and Y. Kawaoka, unpublished data), and NS (K. Fujii and Y. Kawaoka, unpublished data) vRNAs are required for their efficient incorporation into virions, suggesting that packaging of vRNA segments (most likely as a viral ribonucleoprotein complex) is mediated by RNA-RNA interactions occurring in trans among the viral RNA segments. If so, specific incorporation signals within each segment may restrict reassortment, just as functional interactions (e.g., formation of the polymerase complex [12], HA-NA [12,16,21,32,33,38], and cleavable HA-M2 functional associations [10,11,26,36]) restrict the random reassortment of viral proteins. In this context, it is interesting that in both the 1957 and 1968 pandemics, the PB1, HA, and/or NA genes were introduced into human viruses from avian viruses (17), suggesting a possible link between the HA and PB1 RNA segments.…”
Section: Discussionmentioning
confidence: 99%